Security-Enriched Urban Computing and Smart Grid Second International Conference, SUComS 2011, Hualien, Taiwan, September 21-23, 2011. Proceedings - Chang, Ruay-Shiung; Kim, Tai-hoon; Peng, Sheng-Lung (Springer eBooks., 2011)
This book constitutes the proceedings of the Second International Conference on Security-Enriched Urban Computing and Smart Grid, held in Hualien, Taiwan, in September 2011. The 35 revised full papers presented together with two invited papers were carefully reviewed and selected from 97 submissions. Among the topics covered are the internet of things, mobile networks, wireless networks, service-oriented computing, data-centric computing, voice over IP, cloud computing, privacy, smart grid systems, distributed systems, agent-based systems, assistive technology, social networks, and wearable computing.